Differences in stress response between two altitudes assessed by salivary cortisol levels within circadian rhythms in long-distance runners - Tsunekawa, K.; Ushiki, K.; Martha, L.; Nakazawa, A.; Hasegawa, R.; Shimizu, R.; Shimoda, N.; Yoshida, A.; Nakajima, K.; Kimura, T.; Murakami, M. (Scientific Reports, 2022)
There are conflicting reports regarding the efficacy of cortisol as a stress marker in altitude training due to the influence of the circadian rhythm. This study aimed to verify whether the automated measurement of salivary cortisol concentration via sequential sampling could detect the differences in exercise stress between two altitudes. We enrolled 12 elite female long-distance runners living near sea level. For the first higher-altitude camp, the runners lived at 1800 m and trained at 1700 m for 7 days. For the second lower-altitude camp, they lived at 1550 m and trained at 1300 m for 7 days. Their saliva was sequentially collected on the last 2 days during each camp which involved different intensity exercises in the morning and afternoon. The salivary cortisol concentrations were measured using electrochemiluminescence immunoassay. Before dinner, the basal salivary cortisol concentrations were significantly higher in the higher-altitude camp. The rate of change in the salivary cortisol concentration during the morning exercise was significantly higher in the higher-altitude camp than in lower-altitude camp (p = 0.028) despite the same exercise programs and intensities. Salivary cortisol level measurements during the athletes' circadian rhythms could detect the differences in acclimatization and exercise stress between two altitudes.